The Effect of Hypertension on the Risk of Premature Birth: Meta Analysis with Binary Data - Nur'aini, Rizky; Ratnasari, Andika Putri (International Journal of Scientific Research and Management (IJSRM), 2024)
Hypertension in pregnancy is a condition where systolic blood pressure increases to more than 140 mmHg and diastolic more than 90 mmHg. Apart from endangering the mother, hypertension is also dangerous for the fetus. We conducted a meta-analysis of articles on the risk of premature birth in pregnant women with hypertension. The research method was carried out by searching for scientific articles in the PubMed and ScienceDirect databases to see if they contained control cases/cohorts of the influence of hypertension on premature birth with N>200. From the search results, 8 eligible journals were selected, namely those containing the relevant independent variable hypertension. The results show that the risk of premature birth is influenced by pregnant women who experience hypertension = 3.971 (95% CI, 2.567; 6.144) with a random effect model because high heterogeneity was detected (I2 = 98.992%). This shows that hypertension experienced by pregnant women can increase the risk of premature birth by 4 times. Hopefully, these results can improve health policies that enable more appropriate treatment, and for pregnant women to carry out routine early examinations and maintain nutritional intake and a healthy lifestyle.